2015
DOI: 10.1128/iai.00198-15
|View full text |Cite
|
Sign up to set email alerts
|

H-NS Silencing of the Salmonella Pathogenicity Island 6-Encoded Type VI Secretion System Limits Salmonella enterica Serovar Typhimurium Interbacterial Killing

Abstract: The secretion of bacterial toxin proteins is achieved by dedicated machineries called secretion systems. The type VI secretion system (T6SS) is a widespread versatile machine used for the delivery of protein toxins to both prokaryotic and eukaryotic cells. In Salmonella enterica serovar Typhimurium, the expression of the T6SS genes is activated during macrophage or mouse infection. Here, we show that the T6SS gene cluster is silenced by the histone-like nucleoid structuring H-NS protein using a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 99 publications
(176 reference statements)
6
62
0
2
Order By: Relevance
“…cholerae [27], Edwardsiella tarda [28] and S . Typhimurium [29], we speculate that H-NS may be a repressor of the T6SS in EHEC. We thus constructed the deletion mutant of hns in EHEC by replacing hns gene with chloramphenicol resistance cassette using λ Red recombination system [30].…”
Section: Resultsmentioning
confidence: 99%
“…cholerae [27], Edwardsiella tarda [28] and S . Typhimurium [29], we speculate that H-NS may be a repressor of the T6SS in EHEC. We thus constructed the deletion mutant of hns in EHEC by replacing hns gene with chloramphenicol resistance cassette using λ Red recombination system [30].…”
Section: Resultsmentioning
confidence: 99%
“…Ribosomally synthesized bacteriocins and nonribosomally synthesized peptides are potent bioactive compounds. Gramnegative bacteriocins can have antibacterial pore-forming activity as well as nuclease and muramidase activities (46). Nonribosomal peptides reveal versatile antimicrobial activities (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…We were surprised that, in contrast to the E. coli K-12 DH5α or W3110 laboratory strains (this study and ref. 36), the commensal E. coli JB2 strain was resistant to SPI-6 attack, which suggests that a defense mechanism may be present in the commensal strain, such as the presence of a T6SS gene cluster or cross-immunity via a Tai4 homolog. Alternatively, it was shown that resident commensal E. coli and S. Typhimurium may transiently cooperate Feces were collected and plated over time on Salmonella selective medium.…”
Section: Discussionmentioning
confidence: 99%
“…Tae4 induces bacterial lysis by cleaving the γ-D-glutamyl-L-mesodiaminopimelic acid amide bond of peptidoglycan and is toxic when expressed in a laboratory strain of Escherichia coli (34,35). Furthering this idea, it has recently been reported that the SPI-6 T6SS is required for S. Typhimurium to outcompete a laboratory strain of E. coli in vitro (36). However, the contribution of the T6SS antiprokaryotic activity of S. Typhimurium during infection of the gut remains unknown.…”
Section: Significancementioning
confidence: 96%